Efecto de sustitución del olote de maíz sobre los parámetros productivos y bienestar animal en cerdos durante la etapa de recría - López Santana, Pablo Andrés (2019)
In order to evaluate the substitution of different levels of corn cob (0, 6, 8 and 10%) in the diet, on the productive parameters and cortisol levels in pigs in the rearing stage.Twenty-four pigs of both sexes weaned at 30 days were used. An experiment with a completely randomized block design (DBCA) and four treatments was carried out; which were: T1 witness (OM0%); T2 (OM6%); T3 (OM8%); T4 (OM10%). The variables measured were: weekly weight, weight gain, feed conversion, production cost, adjusted conversion, mortality, cortisol levels and cost benefit. The observations were processed through the analysis of variance. The results obtained showed significant differences (p <0.05) for the consumption of food being the lowest consumption for T4 (31.92kg), the other treatments did not present significant differences maintaining a consumption that not less than 34kg. The remaining variables did not show significant differences. Blood cortisol levels were: T1 (266.25mol / l); T2 (259.11 mol / l); T3 (261.54 nmol / l) and T4 (345.94 nmol / l). The profitability obtained was: T1 ($ 1.40); T2 ($ 1.41); T3 ($ 1.23) and T4 ($ 1.18). It is concluded that the substitution of corn flour in the diet did not influence the productive parameters, being an alternative of substitution as a low cost ingredient in the feeding of pigs.